2007
DOI: 10.1002/prca.200700105
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics in ocular fluids

Abstract: The focus of this article is to review recent techniques in proteomic analysis of ocular fluids. These fluids include tears, aqueous humor, and vitreous, they will also be compared to serum analysis. Furthermore, we attempt to summarize some disease correlated biomarkers in ocular fluids that were discovered through different proteomic techniques in eye diseases like dry eye, glaucoma, age-related macular degeneration, uveitis, or diabetic retinopathy. This review is trying to point out the importance of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 122 publications
0
57
0
4
Order By: Relevance
“…Although standard results can be obtained using only capillary tubes, the insistence on using STT for protein analysis is due to the minimal invasiveness of the method, which makes it an interesting option for proteomics studies (Grus et al 2007, Li et al 2008. Besides that, the strip retains ocular surface proteins, considered by some authors an advantage to provide an enriched sample to compare normal and pathological environment if the analysis of the ocular surface is desirable (Li et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although standard results can be obtained using only capillary tubes, the insistence on using STT for protein analysis is due to the minimal invasiveness of the method, which makes it an interesting option for proteomics studies (Grus et al 2007, Li et al 2008. Besides that, the strip retains ocular surface proteins, considered by some authors an advantage to provide an enriched sample to compare normal and pathological environment if the analysis of the ocular surface is desirable (Li et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The main focus in clinical proteomics is the discovery of new proteins or peptides that work as biomarkers correlated to a specific disease (Couture et al 2006, Grus et al 2007, Campos et al 2008. Metalloproteinases were identified in the dog (Couture et al 2006) and equine tears from corneal injury (Ollivier et al 2004), and dogs with cancer showed a different expression pattern of proteins (Campos et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, plasma proteins like albumin, globulins [68], and transferrin [69] are present in the aqueous humour [70]. A study comparing the aqueous humour proteins between DR and control groups shown the upregulation of APOA1, serotransferrin, keratin type I cytoskeletal 9, keratin type I cytoskeletal 10, growth factor receptor-bound protein 10, brain-specific angiogenesis inhibitor 1-associated protein 2 and cystathionine β-synthase, and downregulation of matrix metalloproteinase 13, podocan and selenoprotein P in the DR group [71].…”
Section: Proteomic Methods Applied For Dr Diagnosismentioning
confidence: 99%
“…LL-37 cathelicidin is an α-helix type AMP of the tear fluid mainly produced by the corneal epithelial cells. Similar to the defensins, cathelicidin exerts various antimicrobial [102] and immunomodulatory functions [54] Complement C4b [64] Brain-specific angiogenesis inhibitor 1-associated protein 2 [70] Lysozyme C [38] VEGF [56] Complement C9 [64] Cystathionine b-synthase [70] Lipophilin A [38] Complement factor B [64] MMP-13 [70] Immunoglobulin lambda chain [38] Pigment epithelial-derived factor [64] Podocan [70] Hsp27 [76] Interstitial retinol-binding protein [64] Selenoprotein P [70] β 2 -Microglobulin [76] Inter-α trypsin inhibitor heavy chain [64] Enolase [77] [95]. In addition, it has an important role in re-epithelialization during wound healing [107].…”
Section: The Chemical Barrier Of the Tears As A Possible Source For Bmentioning
confidence: 99%